Islamic Education Learning Strategy In The Era Of Society 5.0 - Fazrurrakhman Al Farisi; Dhiya Wirdatul Izzah; adnan (Journal of Educational Administration, 2022)
This study aims to analyze the educational process of Islamic education in the era of society 5.0. As we know, this. Education is an important part of human life that requires a complex and diverse approach to be implemented effectively. This research uses qualitative methods and literature study. The results of the study show that the Islamic education system and its application to students must be able to create a young generation in accordance with the goals of Pancasila which also has the correct implementation. This research also provides products that can improve the quality of Islamic education by providing freedom of critical thinking and freedom to use information technology in the delivery of educational materials.